The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1139/apnm-2012-0496
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain amino acids alleviate nonalcoholic steatohepatitis in rats

Abstract: Nonalcoholic steatohepatitis (NASH) is a prevalent disease in countries around the world. The branched-chain amino acids (BCAAs) leucine, isoleucine, and valine cannot be synthesized by the body and have been shown to promote muscle buildup; thus, it is logical to suggest that BCAAs can reduce fat deposition in the body. We used gonadectomized rats fed a high-fat diet to investigate the effects of BCAAs on lipid metabolism over an 8-week experimental period. Body composition, tissue histology, plasma lipid ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…BCAAs were reported to reduce hyperlipidemia, hepatic lipid accumulation [8,31,32], and obesity (reviewed by [33]) but the intrinsic mechanism was not clear yet. Indirect evidences include in vivo studies that revealed BCAAs upregulate the lipid catabolic genes carnitine palmitoyltransferase I and PPARα [34] and downregulate the hepatic lipogenic genes acetyl-CoA carboxylase α and stearoyl-coAdesaturase 1 in chicks [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCAAs were reported to reduce hyperlipidemia, hepatic lipid accumulation [8,31,32], and obesity (reviewed by [33]) but the intrinsic mechanism was not clear yet. Indirect evidences include in vivo studies that revealed BCAAs upregulate the lipid catabolic genes carnitine palmitoyltransferase I and PPARα [34] and downregulate the hepatic lipogenic genes acetyl-CoA carboxylase α and stearoyl-coAdesaturase 1 in chicks [35].…”
Section: Discussionmentioning
confidence: 99%
“…The catabolic intermediate of valine, 3-hydroxy-isobutyrate, is a paracrine regulator of fatty acid flux [7]. Feeding high fat diets with the inclusion of BCAA to rodents reduces obesity and hepatocyte fat deposition [8]. In finishing pigs, isoleucine supplementation increase lipogenesis in intramuscular fat [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the supplementation of BCAAs did not improve the liver dysfunction of ob/ob mice. Previous studies reported the beneficial effects of BCAA on hepatic steatosis in NAFLD/NASH mouse models . The discrepancy might be led by differences in model mice or rats.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the beneficial effects of BCAA on hepatic steatosis in NAFLD/NASH mouse models. [34][35][36] The discrepancy might be led by differences in model mice or rats. Leptin-deficient ob/ob mice induced more severe steatosis and liver dysfunction than the diet-induced model.…”
Section: S Trict Evaluation Of the Area Of Lds In Hepato-mentioning
confidence: 99%
“…When animals were fed a high-fat diet to induce an insulin resistance, an increase of protein or amino acid intake has been reported to improve liver steatosis with decreased de novo lipogenesis fluxes, reduced expression of lipogenic genes, lower postprandial insulin secretion, and improved glucose tolerance; this was associated with restored expression of muscle insulin signaling proteins repressed by a high-fat diet [40]. Four-week or 8-week supplementation with leucine reduced fat deposition in liver [41,42] by enhancing VLDL lipid secretion. Chronic leucine supplementation increases insulin sensitivity and body weight likely by reducing oxidative stress and improving insulin signaling pathway in liver, skeletal muscle, and adipose tissue of rats fed high fat diet [43].…”
Section: Effects Of Protein/amino Acid On Glucose Control and Insulinmentioning
confidence: 99%